2001
DOI: 10.1128/mcb.21.4.1121-1131.2001
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation of E2F-p130 and Sp1-pRb Complexes in Repression of the Chinese Hamster dhfr Gene

Abstract: In mammalian cells reiterated binding sites for Sp1 and two overlapping and inverted E2F sites at the transcription start site regulate the dhfr promoter during the cell growth cycle. Here we have examined the contributions of the dhfr Sp1 and E2F sites in the repression of dhfr gene expression. In serum-starved cells or during serum stimulation, the Chinese hamster dhfr gene was not derepressed by trichostatin A (TSA), an inhibitor of histone deacetylases (HDAC). Immunoprecipitation experiments showed that HD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 59 publications
4
31
0
Order By: Relevance
“…2E and 3F to I, ascofuranone had no effect on c-Myc transcription in these cell lines. These results suggest that c-Myc is an upstream repressor of p21 WAF1/CIP1 expression in ascofuranone-treated cells, as has been shown in cells treated with transforming growth factor-β, phorbol ester, and genotoxins (32,33).…”
Section: Ascofuranone Induces P21supporting
confidence: 53%
“…2E and 3F to I, ascofuranone had no effect on c-Myc transcription in these cell lines. These results suggest that c-Myc is an upstream repressor of p21 WAF1/CIP1 expression in ascofuranone-treated cells, as has been shown in cells treated with transforming growth factor-β, phorbol ester, and genotoxins (32,33).…”
Section: Ascofuranone Induces P21supporting
confidence: 53%
“…Under starvation synchronized growth arrest conditions, endogenous E2F may be released and activated. 16,17,18 The result showed that starvation dramatically induced E2F activity in MDA-MB-231 but not in MDA-MB-435 (Figure 2b (Figure 4). In comparison, combinations of Delta24 with Ad/CMV-GFP or Ad/TRAIL-F/RGD with Ad/CMV-GFP did not improve the tumor suppression when compared with groups treated by Delta24 or Ad/TRAIL-F/RGD alone (P40.05).…”
Section: Combination Of Adenovirotherapy and Trail Gene Therapy Enhanmentioning
confidence: 88%
“…The role of all three TFs in cell cycle regulation is well established. 4,9,37,38 In the promoters presented in Figure 1, biologically active BSs emerge as islands of conservation, easily distinguishable from the surrounding sequences. Unfortunately, in most cases the identification of TFBSs is more difficult, either because of differences between the orthologous BSs, or because the BSs lie within long stretches of highly conserved promoter regions.…”
Section: Resultsmentioning
confidence: 99%